Grammar as Phenomenology. Considerations on Wittgenstein’s thought - Fernández, José Ruíz (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This paper tries to clarify the reasons that made Wittgenstein believe that phenomenology had to be accomplished as what he called «grammar». In a second moment, the original discoveries and weaknesses of his grammatical conception of phenomenology will be critically discussed.